Estimation of Above Ground Carbon Sequestration in Trembesi (Albizia saman) and Johar (Senna siamea) at PT Multi Harapan Utama, East Kalimantan - Widya Fajariani; Medi Hendra; Dwi Susanto (Journal of Tropical Biodiversity and Biotechnology, 2020)
The open-pit mining method has a very large ecological impact. It causes the loss of forest vegetation which decreases CO2 absorption. Measuring the amount of carbon stored in plant biomass can represent the amount of CO2 that can be absorbed in the atmosphere. The objective of this research is to determine the carbon sequestration of Albizia saman and Senna siamea in different age classes at PT MHU Busang Jonggon Block, Kukar, East Kalimantan. Estimation of carbon sequestration in the stands of A. saman and S. siamea was carried out by non-destructive methods using biomass allometric equations while in understorey and litter using the destruction sampling. The results showed that the highest carbon absorption value of A. saman was 314.28 tons/ha which appear at six years old stands and the lowest value was 193.31 tons/ha at three years old stands while the highest carbon absorption value of S. siamea was 113.65 tons/ha which appear at nine years old stands and the lowest value was 24.64 tons/ha at three years old stands. A. saman could be more promising plant species than S. siamea according to its higher level of carbon sequestration and their high adaptation level. All data from this study could suggest several information for increasing carbon sequestration level in forest ecosystem as well as achieving forest rehabilitation purpose.